2001
DOI: 10.1007/s002440010164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atrazine and Nicosulfuron on Phytoplankton in Systems of Increasing Complexity

Abstract: We have tested the sensitivity of phytoplankton to the herbicides atrazine and nicosulfuron in experiments conduced in increasingly complex systems, from single strain phytoplankton cultures (microplates) to mesocosms mimicking whole ecosystems. The endpoints used to assess sensitivity to atrazine and nicosulfuron were total biomass increase, photosynthetic efficiency, and community diversity, depending on the system considered. Nicosulfuron appeared to be very much less toxic to phytoplankton than atrazine, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Another study found the triazine atrazine to be more toxic to the chlorophytes than to diatoms (Seguin et al, 2001). From the data available in literature, it is still unclear whether diatoms are more sensitive to triazine than other microalgae, since this sensitivity can vary depending on the herbicide (Suresh Kumar et al, 2014) and the diatom species (Larras et al, 2014).…”
Section: Herbicide Toxicity Towards the Two Wild Strainsmentioning
confidence: 98%
“…Another study found the triazine atrazine to be more toxic to the chlorophytes than to diatoms (Seguin et al, 2001). From the data available in literature, it is still unclear whether diatoms are more sensitive to triazine than other microalgae, since this sensitivity can vary depending on the herbicide (Suresh Kumar et al, 2014) and the diatom species (Larras et al, 2014).…”
Section: Herbicide Toxicity Towards the Two Wild Strainsmentioning
confidence: 98%
“…Such systems give a view of the whole community, including populations that are hard to maintain; they can thus provide a wider survey of organism sensitivity for toxicants (Yasuno et al 1993). Leboulanger et al (2001) and Seguin et al (2001) pointed out the need for reliable toxicity data from such microcosm systems.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental concentrations of the sulfonylurea herbicides in these surface waters were, in all studies, less than 1 µg L −1 . However, concentrations of sulfonylurea herbicides in the range of 0.4 to 2 µg L −1 have been shown to affect some algae species (Nyström et al, 1999;Seguin et al, 2001;Couderchet and Vernet, 2003;Vulliet et al, 2004) as well as the macrophyte Lemna minor (Fairchild et al, 1999;Vulliet et al, 2004). Chlorsulfuron, metsulfuron-methyl (Nyström et al, 1999;Fairchild et al, 1999), and triasulfuron (Vulliet et al, 2004) affected both algae and Lemna minor, whereas flazasulfuron (Couderchet and Vernet, 2003), nicosulfuron (Seguin et al, 2001), bensulfuron-methyl, and imazosulfuron (Ishihara, 2009) were shown to affect algae.…”
Section: Spring To Fallmentioning
confidence: 99%